2012
DOI: 10.1007/s00134-012-2628-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of inhaled colistimethate sodium (CMS) in mechanically ventilated critically ill patients

Abstract: Inhaled colistin may achieve high drug concentrations in the lung. However, a dose of 80 mg of inhaled CMS every 8 h may not be adequate for the treatment of lower respiratory tract infections due to multi-drug resistant GNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 29 publications
5
95
1
7
Order By: Relevance
“…In addition, recent studies revealed that nebulized colistin, as adjunctive therapy simultaneously administered with intravenous colistin, was significantly associated with improved rate of clinical cure and reduced duration of mechanical ventilation without noticeable adverse events in patients with VAP due to CRAB (8,9). The use of nebulized colistin in critically ill patients may be supported by previous reports suggesting that it effectively achieved high concentrations in the lungs, with minimal systemic exposure (10,11). However, there is a paucity of data to evaluate the efficacy of nebulized colistin as monotherapy for pneumonia of multidrugresistant gram-negative bacteria (12)(13)(14).…”
Section: Introductionmentioning
confidence: 73%
“…In addition, recent studies revealed that nebulized colistin, as adjunctive therapy simultaneously administered with intravenous colistin, was significantly associated with improved rate of clinical cure and reduced duration of mechanical ventilation without noticeable adverse events in patients with VAP due to CRAB (8,9). The use of nebulized colistin in critically ill patients may be supported by previous reports suggesting that it effectively achieved high concentrations in the lungs, with minimal systemic exposure (10,11). However, there is a paucity of data to evaluate the efficacy of nebulized colistin as monotherapy for pneumonia of multidrugresistant gram-negative bacteria (12)(13)(14).…”
Section: Introductionmentioning
confidence: 73%
“…Almost all modern PK studies on polymyxins are for colistin that is administered parenterally as its inactive prodrug CMS (77,82). In contrast, polymyxin B is available for direct parenteral administration, that is, as the antibacterial entity (83).…”
Section: Dosing Strategiesmentioning
confidence: 99%
“…PK studies reporting antibiotic concentrations in the lung compartments using nebulization are becoming increasingly reported. 45,46 Athanassa et al 45 evaluated 20 critically ill patients with ventilator-associated tracheobronchitis treated with nebulized colistin. After the first nebulization, the median ELF concentrations were 6.7 and 2.0 mg/L at 1 and 8 hours, respectively.…”
Section: Alternative Dosing Strategies: Nebulizationmentioning
confidence: 99%
“…concentrations can be achieved in the ELF with nebulization, 45 which suggests improved target site concentrations with nebulization. Luyt et al 46 similarly showed favorable amikacin concentrations in ELF in a study of 28 mechanically ventilated patients with gram-negative VAP.…”
Section: Alternative Dosing Strategies: Nebulizationmentioning
confidence: 99%
See 1 more Smart Citation